Determination of the transiently lowered pKa of the retinal Schiff base during the photocycle of bacteriorhodopsin. - Brown, L S (1996)
Reprotonation of the transiently deprotonated retinal Schiff base in the bacteriorhodopsin photocycle is greatly slowed when the proton donor Asp-96 is removed with site-specific mutagenesis, but its rate is restored upon adding azide or other weak acids such as formate and cyanate. As expected, between pH 3 and 7 the rate of Schiff base protonation in the photocycle of the D96N mutant correlates with the concentrations of the acid forms of these agents. Dissection of the rates in the biexponential reprotonation kinetics of the Schiff base between pH 7 and 9 yielded calculated rate constants for the protonation equilibrium. Their dependencies on pH and azide or cyanate concentrations are consistent with both earlier suggested mechanisms: (i) azide and other weak acids may function as proton carriers in the protonation equilibrium of the Schiff base, or (ii) the binding of their anionic forms may catalyze proton conduction to and from the Schiff base. The measured rate constants allow the calculation of the pKa of the Schiff base during its reprotonation in the photocycle of D96N. It is 8.2-8.3, a value much below the pKa determined earlier in unphotolyzed bacteriorhodopsin.